Vocational Education and Training in the Light of the Reforms of Polish Education System in the Years 1999–2017 - Kust, Izabella (Przegląd Badań Edukacyjnych (Educational Studies Review), 2020)
Vocational education and training (VET) is subject to permanent transformation, which results from the need to adapt it to the labour market and implement new technologies, as well as from globalisation, membership in the European Union, and modernisation of education systems. The aim of this article is to present changes in vocational education and training in Poland in the years 1999-2017 and their consequences. The results included, among other things, phasing out vocational education and training in favour of general education, which clearly deprived the labour market of qualified specialists. Bringing back the prestige of vocational education is currently one of the priorities of the state’s education policy. This attempt requires the involvement of various stakeholders, not only school community and educational circles, but also employers. The need to build a positive image of vocational education and training in society, both at the level of secondary and sectoral vocational schools offering training in blue collar jobs, which are in high demand in the labour market, currently poses a social challenge.